The 45 K Onset Superconductivity and the Suppression of the Nematic Order in FeSe by Electrolyte Gating*Supported by the National Natural Science Foundation of China under Grant Nos 11174294, 11174291, 11374302, 11304319, U1332209, U1432251 and U1532153, the China Postdoctoral Science Foundation under Grant No 2015M582020, the Program of Users with Excellence, the Hefei Science Center of Chinese Academy of Sciences, and the CAS/SAFEA International Partnership Program for Creative Research Teams of China. (May 2016) - Wang 王, Wei-Ke 伟科; Liu 刘, Yan 艳; Yang 杨, Ji-Yong 继勇; Du 杜, Hai-Feng 海峰; Ning 宁, Wei 伟; Ling 凌, Lang-Sheng 浪生; Tong 童, Wei 伟; Qu 屈, Zhe 哲; Yang 杨, Zhao-Rong 昭荣; Tian 田, Ming-Liang 明亮; Zhang 张, Yu-Heng 裕恒
Abstract : The electronic doping effect on both the superconductivity and the nematic order in the FeSe nanoflake are investigated by using the electric-double-layer transistor configuration. The superconductivity can be effectively controlled by electronic doping, and the onset superconducting transition temperature Tc reaches as high as 45 K at a gate voltage of Vg = 4 V. Meanwhile, the nematic phase is gradually suppressed with the increase of electronic doping (or Vg ). The results provide an effective method with variable charge doping for investigation of the rich physics in the FeSe superconductor.